1955
DOI: 10.1039/jr9550003864
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine and related compounds. Part XIV. Structure of β- and γ-lumicolchicine

Abstract: Colchicine a i d Related Compounds. Part X W . * Structure of pand y-lumicolchicine.By E. J. FORBES.[Reprint Order No. 6528.1The action of sunlight on dilute aqueous solutions of colchicine leads to the formation of a-, p-, and y-lumicolchicine, each isomeric with colchicine (Grewe and Wulf, Chem. Bey., 1951, 84, 621). Degradative and spectroscopic evidence suggests that @and 7-lumicolchicine are stereoisomers and indicates that they have tetracyclic structures which arise from a rearrangement of the bonds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1965
1965
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In 1951, Grewe and Wulf reported that the exposure of dilute aqueous solutions of colchicine to sunlight for 5–7 weeks gave a mixture of α‐, β‐ and γ‐lumicolchicines (Scheme ), with all three products being obtained in similar amounts, although the structures of the products were not reported . Subsequently, Forbes repeated the experiment, obtaining the same three products, although this time β‐lumicolchicine was obtained as the major product . The structures of the β‐ and γ‐lumicolchicines ( 51a and 51b ) were elucidated by Forbes, by Gardner and co‐workers, and by Chapman and co‐workers, confirming that both products arise from a Type C photocyclization, and that they are diastereoisomers of each other.…”
Section: Cycloheptatriene Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1951, Grewe and Wulf reported that the exposure of dilute aqueous solutions of colchicine to sunlight for 5–7 weeks gave a mixture of α‐, β‐ and γ‐lumicolchicines (Scheme ), with all three products being obtained in similar amounts, although the structures of the products were not reported . Subsequently, Forbes repeated the experiment, obtaining the same three products, although this time β‐lumicolchicine was obtained as the major product . The structures of the β‐ and γ‐lumicolchicines ( 51a and 51b ) were elucidated by Forbes, by Gardner and co‐workers, and by Chapman and co‐workers, confirming that both products arise from a Type C photocyclization, and that they are diastereoisomers of each other.…”
Section: Cycloheptatriene Systemsmentioning
confidence: 99%
“…Subsequently, Forbes repeated the experiment, obtaining the same three products, although this time β‐lumicolchicine was obtained as the major product . The structures of the β‐ and γ‐lumicolchicines ( 51a and 51b ) were elucidated by Forbes, by Gardner and co‐workers, and by Chapman and co‐workers, confirming that both products arise from a Type C photocyclization, and that they are diastereoisomers of each other. The third product, α‐lumicolchicine, is obtained through [2+2] photocycloaddition of β‐lumicolchicine upon extended irradiation …”
Section: Cycloheptatriene Systemsmentioning
confidence: 99%
“…Ultraviolet irradiation causes the conversion of colchicine to ~?-and 7-1umicolchicine [17][18][19][20]. This photo-induced rearrangement occurs at the C-ring part of colchicine ( fig.…”
Section: Effect Of the B-ring On Photo-induced Rearrangement Of The Cmentioning
confidence: 99%
“…When exposed to sunlight, colchicine undergoes a photochemical rearrangement to give a, ß, and y lumicolchicines (3,4) (Fig . 1) .…”
Section: Introductionmentioning
confidence: 99%